CARING FOR THE EARTH WITH EDUCATION: INTEGRATING QUR'ANIC VALUES IN EARLY CHILDHOOD EDUCATION - ulya, miftah; Ari Masyhuri, Ahmad; Chairunnisa, Chairunnisa; Bakir, Moh.; Muchammad, Achmad (LPPM Institut Agama Islam Diniyyah Pekanbaru, 2025)
Abstract Early childhood education (ECE) plays an important role in shaping children's character and values from an early age. The integration of Qur'anic values in ECD can provide a strong moral and spiritual foundation for children. This article explores how Qur'anic values can be integrated in the ECD curriculum to care for the earth and support sustainable development. This research method is Library Research using a qualitative approach through textual and contextual analysis of Quranic verses. The discussion is descriptive by describing, explaining, and reporting a situation. Furthermore, various terms are arranged based on the deductive and inductive approaches. Through the deductive approach, it is hoped that it can provide answers from the Qur'an to the identification of relevant Qur'anic values and their integration strategies in the Early Childhood Education curriculum. The results show that Qur'anic values such as responsibility as khalifah on earth (Surah Al-Baqarah [2]: 30), the importance of protecting the environment (Surah Ar-Rum [60]: 41), and social justice (Surah An-Nisa [4]: 135) can be integrated in various aspects of early childhood education. Integration strategies including project-based learning, play activities that support environmental awareness, and a holistic approach that includes spiritual, moral, and social aspects are needed in grounding education in Early Childhood Education. The integration of Qur'anic values in Early Childhood Education can raise children's awareness about the importance of protecting the environment and caring for the earth. Sustainability-focused education can shape a generation that is more responsible and committed to preserving nature. Challenges in implementation include the need for training for educators and provision of adequate resources. From the foregoing it can be concluded that integrating Qur'anic values in early childhood education is an important step towards shaping the character of children who care about the environment and support sustainable development. This approach not only provides a strong moral foundation but also helps create a better future for future generations.